Arte, educaç\~ao e a prova do pudim: Entre os direitos públicos subjetivos e a efetividade das políticas da arte - Érica Coutinho; Frederico Barbosa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This work seeks to undo any duality between cultural rights and the right to education and between popular culture and fine arts, in order to better visualize the structure of a political public art education. Respecting to the first duality, what is pursued is the building of an argumentative horizon, which comprises cultural rights, and the right to education based on the historicity of human rights language and the design of legal doctrine regarding the subjective public rights. Regarding the second duality, popular culture/fine arts, the aim is to break it from the concept of aesthetic experience, developed by the American pragmatist philosopher John Dewey. Through this concept, the meaning of art is displaced as related to the sublime, then located it as a holistic experience, once individual and collective. Such aesthetic experience is related to principles such as individual autonomy and the right training sharing symbolic goods produced by the community that are also present in education. Once these dualities are unweaven, this dissertation seeks to question whether the cognitive and normative senses of political art education, structured in the Ministério da Educaç\~ao e Cultura (MEC), are aligned to an instrumental policy. In this work, the instrument is the presentation model that sees the effectiveness of public policy in the relationship between adherence to their territory and their ability to institutionalization. The territoriality is the central dimension that allows the testing of fairness and strength of institutionalization of problems responses. Therefore, this dissertation demonstrates quantitative indicators in the form of maps that allow quick view of the state and economic policies with special focus on the formation of the arteducator.
Keywords: Z18; H80; I28; 330; Public Policy; Subjective public right; Art education; Philosophical pragmatism